Assessment of arsenic contamination of milk and dairy products - Chuyen Van Nguyen; Ba Van Nguyen; Trung Hoang Nguyen; Trang Thi Thu Nguyen; Truong Thi Hoang; Minh Duc Tong; Anh Tuan Le; Hang Thi Dieu Dinh; Chinh Dinh Vu; Dien Duc Nguyen (Revista Cubana de Medicina Militar)
Introduction: Milk and dairy products are nutritious and can play a significant role in a healthy diet. The safety of milk decreases with increasing concentration of arsenic. The Maximum Residue Limits of arsenic is 500 parts per billion (ppb). Objectives: To evaluate the status of arsenic contamination of milk and dairy products produced and processed in some provinces and cities of Vietnam. Methods: A total of 367 samples were tested. Samples were digested before analysis to remove organic compounds, and the total arsenic content determined by atomic absorption spectrophotometry. Results: The average concentrations of total arsenic in liquid milk were 139.32 ppb; in yogurt, 169.81 ppb; in cheese, 221.38 ppb; in milk cake, 232.80 ppb; and in milk powder, 35.43 ppb, respectively. Conclusion: The arsenic concentrations in some samples are higher than the maximum permitted levels according to national regulations.